The macroeconomics of liquidity in financial intermediation - Davide Porcellacchia; Kevin D. Sheedy (European Central Bank (ECB), 2024)
In financial crises, the premium on liquid assets such as US Treasuries increases alongside credit spreads. This paper explains the link between the liquidity premium and spreads. We present a theory of endogenous bank fragility arising from a coordination friction among bank creditors. The theory's implications reduce to a single constraint on banks, which is embedded in a quantitative macroeconomic model to investigate the transmission of shocks to spreads and economic activity. Shocks that reduce bank net worth exacerbate the coordination friction. In response, banks lend less and demand more liquid assets. This drives up both credit spreads and the liquidity premium. By mitigating the coordination friction, expansions of public liquidity reduce spreads and boost the economy. Empirically, we identify high-frequency exogenous variation in liquidity by exploiting the time lag between auction and issuance of US Treasuries. We find a causal effect on spreads in line with the calibrated model.
Keywords: E41; E44; E51; G01; G21; 330; bank runs; bank-lending channel; liquid assets